Impacts of land use on water quality of Similajau National Park, Bintulu, Sarrawak : a case for integrated water resources management - Abdul Wahab, Bin Haji Bujang (Universiti Malaysia Sarawak (UNIMAS), 2001)
Wateros considered as one of the most important componentmf the ecosystem. The conditions of the water resource within and flows through the drainage systems of the Similajau National Park determine the long~term ecological intergrity of the Park. The appropriate planning approach and desired management interventions must be designed and aligned towards the maintenance of envirmUllent water quality requirement for sustainability of the overall ecosystem functions. A study was undertaken from the month of May to August 2001 to characterize the watershed geomorphology and hydrology of the Sebubung and Seroba Watersheds, and assessment of water quality of the two rivers namely Sebubung River and Seroba River. The rivers flow through the Park prior to discharging their waters into the South China Sea. The upstream and the headwaters of the two rivers lie outside the Park, one within the newly established oil palm plantation and the other logged over area, respectively. Thirty water samples were collected and analyzed for Total Suspended Solids (TSS) Suspended Solids, Total Coliform, fecal Coliform, Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), and Nutrients (Ammonical Nitrogen and Phosphate). In~ Situ measurements for Dissolved Oxygen (~O), Temperature, pH, Total Oisolved Solids (TDS), Salinity, Oxidation Reduction Potential (ORP), and Turbidity were conducted at eight sampling points, five along Sebubung River and three along Seroba River. This study indicates that the TSS, Turbidity, BOD, and COD of the water of Sebubung River whose upstream zone and head waters currently under active establishment stage of conversion to oil~palm plantation, exhibited higher mean values relative to the water of Seroba River. Mean TSS and Turbidity under low flow recorded at sampling points WSB I 158.67 mg/L, WSB3 188.67 mg/L, WSB5 52.0 mglL, and WSB6 72.0 mglL. However, comparative analysis between water quality of Sebubung River and Seroba River indicated that only turbidity and TSS were significantly different at 95% confident level.